Political dynamics and electoral oversight in Indonesia: An evaluation of Bawaslu’s role in upholding democracy - Puadi; Romli, Lili; Jalal, Asran (International Journal of Innovative Research and Scientific Studies, 2025)
A democratic and integrity-based election is a fundamental pillar in establishing governance under the rule of law. In Indonesia, the Election Supervisory Agency (Bawaslu) plays a strategic role in ensuring that elections are conducted fairly, transparently, and honestly. This study evaluates the role of Bawaslu in overseeing the electoral process amid complex political dynamics. A qualitative research approach was employed through literature analysis and a case study of the 2019 simultaneous elections. The findings indicate that Bawaslu faces challenges related to independence, the effectiveness of supervision, and the enforcement of electoral laws. These findings reaffirm that Bawaslu’s existence is crucial in safeguarding the integrity of democracy, but it still requires strengthening in terms of regulatory frameworks and institutional capacity.